Ultrasonography Findings of Breast Microcalcifications without Accompanying Mass and Evaluation of Ultrasound-Guided Biopsy Results - Durhan, Gamze; Önder, Ömer; Azizova, Aynur; Karakaya, Jale; Kösemehmetoğlu, Kemal; Akpınar, Meltem; Demirkazık, Figen (Acta Medica, 2020)
Objective: Ultrasonography guided core needle biopsy is a real-time, inexpensive method with higher patient comfort. The aim of this study was to evaluate ultrasonography findings of microcalcifications without accompanying mass and also to investigate the accuracy of ultrasonography guided core needle biopsy results. Materials and Methods: The study included a total of 54 patients, with microcalcifications observed on mammography and no accompanying mass, who underwent ultrasonography guided core needle biopsy and surgical excision. Core needle biopsy specimen x-rays were obtained from 23 patients. In 11 patients, the location of microcalcification was confirmed by mammography following the administration of contrast agent under ultrasonography guidance. Ultrasonography findings of microcalcifications were identified. The results of ultrasonography guided core needle biopsy were compared with the excisional pathology results. Results: The microcalcifications without accompanying mass were presented with punctate echogenous foci, hypoechoic area, small distortion, ductal abnormality or fibrocystic changes on ultrasonography. Hypoechoic area and distortion were seen more in malignant lesions, and fibrocystic changes and ductal abnormalities in benign lesions but the difference was not statistically significant. The agreement between ultrasonography guided core needle biopsy and the excisional pathology results was high (Kappa = 0.781). When a specimen x-ray was obtained or core needle biopsy was performed after confirming the location of the microcalcifications with the use of contrast agent, Kappa values were even higher (0.87 and 1, respectively). Conclusions: Microcalcifications can be seen with targeted ultrasonography imaging and ultrasonography guided core needle biopsy has high accuracy. Taking a specimen x-ray, or biopsy performed after identifying of the location of microcalcifications with a trace amount of contrast agent, can increase the accuracy of ultrasonography guided core needle biopsy.